The Influence of Service Quality, Price Perception and Customer Satisfaction on Customer Loyalty in UD. Mujur 2 - Ahmad Efendi Cahyo Setiono, AHMAD; Hakimah, Ema Nurzainul (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research Objectives: This study aims to determine the influence of service quality, price perception, and customer satisfaction on customer loyalty both individually and simultaneously in UD. Mujur 2 Kediri. Design/Methods/Approaches: This study uses a quantitative methodology involving surveys to explore the influence of service quality, price perception, and customer satisfaction on customer commitment at UD. Mujur 2 Kediri. The research sample included 58 participants, selected by purposive sampling, these participants had purchased the product more than twice. Data were collected through direct observation and questionnaires, then analyzed with SPSS 23 using instrumentation, classical theory, multiple linear regression, and hypothesis testing. Research Findings: The results of the study show that service quality, price perception, and customer satisfaction have a positive and significant effect on customer commitment both directly and indirectly to UD. Mujur 2 Kediri. Theoretical contribution/Originality: This research helps develop customer commitment theory and provides a deeper understanding of the various ways in which different aspects of the building industry affect customer loyalty. Implications for Practitioners/Policy: This research has practical applications that can be used by building managers to improve service quality, set appropriate prices, and ensure customer satisfaction. The results of this research can be directly applied to business strategies that increase customer commitment and improve store performance. Research limitations: This research was only conducted at UD.Mujur 2 Kediri, so the findings obtained may not fully describe the condition of the shopping industry in general. A wider sample or research in several shops in other areas can provide more representative results